Taxonomy of Economic Groups: A Proposal for Tax Supervision on High-Net-Worth Individuals (HNWI) in Indonesia - Hutasoit, Erikson Aprianto Hotmangatur; Permana, Djaka; Wulandari, Florentina Ratih (International Journal of Science and Society, 2024)
High Net Worth Individual (HNWI) is defined as an individual who has wealth or income on the highest scale. The role of HNWIs in a country's economy is very significant. However, in 2022 the contribution of tax revenues from all individuals (Income Tax Article 25/29 Individuals) in Indonesia will only reach 0.68% of the total national net tax revenues. In this writing, the authors aim to evaluate the effectiveness of the tax supervision policy performance of the Individual Taxpayer in Indonesia. The method used is using a descriptive qualitative approach through case studies using primary data in the form of interview results. Based on this writing, supervision of HNWIs in Indonesia is known to be not optimal. Where the supervision carried out has not been able to mitigate the risk of using Aggressive Tax Planning which, among other things, can be carried out by HNWIs using names other than the name concerned in disguising ownership of assets or income. This writing finds the most significant enabler in optimizing HNWI tax supervision is through the identification of HNWI income streams which in this writing are grouped into 8 (eight) nodes depicted in a diagram which the authors call "Taxonomy of Economic Groups". This writing finds that the risk treatment for this risk event is by changing the provisions of Article 18 paragraph (4) of the Income Tax Law.